Analisis Preferensi Konsumen Muda terhadap Iphone di Kota Bandung - Osa Omar Omar Sharif; Lita Hartalita (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2017)
This research aims to determine theconsumer preferences on iPhone’s attributes in Bandung 2015. Researcher used five attributes which are: durability, operating system, screen size, camera, and RAM. Research method used in this study is a descriptive method, by using nonprobability sampling techniquewith a sample of 387 respondents. This paperusing conjoint analysis for smartphone users which are interested usingiPhone in Bandung to find the most wanted iPhone preference by consumers. The results indicate that all respondents generally making durability attributes as the main preference in choosing an iPhone. Based on the conjoint analysis it can be seen thatiPhone that consumers want is more than five years durability, iOS 8 for its operating system, 5.5 inches for its screen size, two gigabytes RAM capacity, and 12 megapixels of camera resolution.